Biopolymer Composites as an Alternative to Materials for the Production of Ecological Packaging - Prochon, Miroslawa (Polymers (Basel), 2021)
The problem of plastic waste has long been a concern for governments and society. However, huge amounts of plastic are still being released into the oceans and the environment. One possible solution is to replace plastics with materials that are more both biodecomposable and biodegradable. The most environmentally friendly materials are made of natural ingredients found in nature, although not all of them can be called biodegradable. In this study, we set out to create a new composite with functional properties that could replace commonly used disposable packaging. To ensure the competitiveness of our solution, we used inexpensive and readily available components, such as gelatin G HOOCCH(2)CH(2)C(R(1))NHCOCH(2)NH(2) (where R(1) is a continuation of the peptide chain), polyvinyl alcohol PVA CH(2)CH(OH), and glycerin G HOCH(2)CH(CH(2)OH)O. The ingredients used in the research come from natural sources; however, they are chemically processed. Some of them, such as polyvinyl alcohol, for example, are biodegradable. With the appropriate selection of the components, in the casting process, the intermixed components made it possible to produce materials that were characterized by good physicochemical properties, including thermal stability, optical transmission of UV-Vis light, cross-linking density, and mechanical strength. The most favorable parameters of thermal stability were observed in casein-containing gelatine forms. The best cross-linking density was obtained in the case of gelatin–glycerine systems. Composite containing caseins distinguished by the highest resistance to flammability, increased thermal stability, flexibility, and greater hardness compared to other composites.